(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Some of the major human health problems being confronted in this era are cardiovascular disease, diabetes and obesity. It is recognized that having proper dietary habits is the best methods for reducing the risk of cardiovascular disease.Aim: To observe the dietary habits of medical students.Materials and Method: This Cross sectional study was conducted in the Department of Public Health and life sciences, University of South Asia, Dhaka from January 2021 to June 2021. 200 medical students of Parkview Medical College age ranging from 18-23years are considered as study group. A structured questionnaire was used to collect and record the information on age, sex & dietary habits. Results: The result observed that out of 200; 57 students (28.5%) didn’t take fruits as snacks, 63 students (31.5%) preferred fast food weekly 3-4times and 96 students (48%) preferred fast food sometimes. Among 200 study population 96 students (48%) drink tea/ coffee once a day, 83 students (41%) twice a day and 178 study subjects (89%) preferred mix veg and non-veg diet. Out of 200 students, 173 students (86.5%) take main meal 2times/day, 66 students (33%) take breakfast within 8am, 103 students (51.5%) take breakfast within 9am, 17 students (8.5%) take breakfast within 10am, 14 students (7%) take breakfast after 10am, 22 students (11%) take lunch at1pm, 76 students (38%) take lunch at 2pm, 79 students (39.5%) take lunch at 3am, 30 students (15%) take dinner at 9pm, 106 students (53%) take dinner at 10pm and 64 students (32%) take dinner after 10pm.Conclusion: The study found that, most of the students, in general, had nearly healthy eating habits except in frequency of meals, fruit and vegetable consumption and consumption of fatty and junk foods but the timing and number of meal is not satisfactory. Despite, being aware of the importance of a proper dietary habit on health, the medical students nevertheless, did not implement theory into practice properly. J Med Coll Women Hosp.2026; 22(1): 34-41